PEDAGOGICAL ACTIVITY IN THE FORMATION OF PROFESSIONAL COMPETENCE - Shermamatova Mohidil (The Conference Hub, 2025)
The article describes all the components of professional activity, the most complete psychological forms of professional development of a person in the process of professional self-government, the features of the development of professional competence, several types of professional competencies that future educators achieve professional integrity in the educational process of a higher educational institution.
Keywords: professional competence, professional activity, motivational, purposeful, content-instrumental, reflexive-Assessment, special competence, social competence, personal competence, individual competence, basic competencies.